INVESTIGATION OF MULTIPHASE CONDITION IN PIPELINE USING GAMMA COMPUTED TOMOGRAPHY - Bayu Azmi; Megy Stefanus (GANENDRA Majalah IPTEK Nuklir, 2019)
INVESTIGATION OF MULTIPHASE CONDITION IN PIPELINE USING GAMMA COMPUTED TOMOGRAPHY. Deposition of sand particles in pipeline is a problem that often occurs in the production and distribution of oil and gas. It could cause increased preasure, equipment failure, pipeline erosion, and production decline. It is very necessary to investigate inside condition of the pipeline without interrupting the operation. Gamma computed tomography (CT) is a technique that can image the internal structure of an object without interrupting or damaging the object (non-destructive testing). This paper presents a preliminary experimental study of multiphase (solid, liquid, and gaseous) condition inside a horizontal pipe using gamma CT technique. A collimated Cs-137 source with 3.7 GBq activity emited gamma photons to penetrate a 14 inches diameter horizontal pipe containing sand, water, and gasoline. The photons that penetrated object were detected using a scintillation detector at the other side of object. The scanner system performed translation and rotation scans to get 64 projection data which will then be reconstructed into an image. The reconstructed images were able to show the pipe wall and the condition of the inside of pipe which was filled with sand, water, and gasoline. The pixel value is linear to material density with R2= 0.9543. The result indicated the potential of gamma CT as the suitable technique to be used to investigate the multiphase conditions in pipeline.